Ethical issues in the prevention of H1N1: the Malaysian experience - Sasidharan, Sreenivasan; Parthiban, S Gopal; L. Jothy, Subramanion; Yoga Latha, Lachimanan (Elsevier, 2012)
Tefhfeic nieonvtelly Hin1N t1h ein hfluumenazna pvoirpuusl athtiaotn e mwietrhg egdlo ibna lh usmpraenasd inh aMs ebxeiceon idne ecalarlrye d2 0a0 9p aanndd etrmaincs mstirtateind boryi gWinHalO d. aHtae rreel awteed r etov itehwe eedth tihcea l rioslseu eosf ient hthicea pl riesvseunet iionn tohfe d pisreeavseenst i(pounb olifs hHe1dN 119. 9S6t-u2d0i1e2s) wweitrhe iisdseunetsif iiend t hveia p sreevaercnhtiionng oefl edcistreoansiecs dmautasbt absee su ntod eerxsttoraocdt. rTehliast ecdo minpfroirsmesa twioonrk. Tohne h roowle t hoef seothciiceatyl uunnddeerrssttaannddsin agb ofeuetd as dinisteoa shee aalnthd dwahmata gairneg t hoeri rh ienadltihv idpuroamlso’ ttiansgk sb etoh acvoinoqr uwehr itchhe eovuetbnrteuaakll.y S wucilhl htheelp v ainri othues cimonptlreoml menetaastiuorne so tfh vaatr mioauys bdeis teaakseen c toon ftirgohl tm theea sduarnegs.e rT ohfe pparnodmeimseisc Hof1 eNt1h iacrael girsesaute.